Bioprospecting of selected wild mushrooms from the tribal zone of Northwest Himalaya, India - Sharma, Neha; Tapwal, Ashwani; Sharma, Neha; Negi, Pitamber Singh (Mushroom Research, 2023)
Fourteen wild edible and medicinal mushrooms representing ten families were collected in an altitude range of 1,867-4,187 metres above sea level form Kinnaur district of Himachal Pradesh, NW Himalaya. The biochemical analysis of sporocarps revealed that the carbohydrate content was maximum in Coprinus comatus and protein was highest in Auricularia auricula-judae, while the fibre content was recorded highest in Ganoderma lucidum. The energy value was determined using the amount of carbohydrates, protein, and fats present in the sporocarps. It was highest in Helvella lacunosa and lowest in G. lucidum. The ash content of sporocarps was used to estimate the mineral composition. The ash content was highest in the sporocarps of S. crispa, closely followed by L. perlatum, R. brevipes, and lowest in R. stricta. The potassium, phosphorus, magnesium and calcium content in general was recorded higher in majority of mushrooms as compared to zinc, manganese, copper, etc. Despite the variations in nutrient content, these mushrooms appear to have a good overall nutritional profile. They have the potential to greatly fulfil people’s requirement of proteins, and macro and micronutrients. Therefore, mushrooms should undoubtedly be included in our diets on a more regular basis to improve the quality of our current diets.